Implementing a Qur’anic Values Inculcation Model at Ummul Quro Integrated Islamic Senior High School, Bogor: (Implementasi Model Penanaman Nilai-Nilai Al-Qur'an di SMA Islam Terpadu (SMAIT) Ummul Quro Bogor) - Lubna Yusuf; Endin Mujahidin; Nesia Andriana (PT. Berkah Smart Academica, 2024)
This study aims to analyze the model of inculcating Qur’anic values implemented at SMA IT Ummul Quro Bogor. The research employs a qualitative approach using a descriptive case study method. Data were collected through in-depth interviews, observations, and documentation involving the Head of Tahsin and Tahfidz Division as well as relevant teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the inculcation of Qur’anic values at SMA IT Ummul Quro Bogor is carried out systematically and in an integrated manner through a syāmil (comprehensive) curriculum involving both students and educators. The implementation is realized through tahfidz and tahsin programs, Qur’an specialization (takhassus), Islamic personal development, leadership programs, and the integration of Qur’anic values across all subjects. Teacher competency is strengthened through continuous coaching, talaqqi, ziyadah, and regular memorization assessments. This model is supported by ongoing academic supervision, the standardized Cahayaku (Nuuri) method, and a conducive school culture. The level of implementation success reaches approximately 95%, as reflected in memorization completion, recitation quality, and the formation of students’ Qur’anic character. This model is considered effective and has the potential to be replicated in Islamic schools with similar visions and missions.